Innovación tecnológica y el impacto en el ámbito secretarial en las oficinas de la Procuraduría Síndica del Gobierno Autónomo Descentralizado del cantón Vinces - Cedeño Muñoz, Cinthia Grisla (2022)
Technological innovation in the secretarial field is very important within a company as the development of technology has concorded the way of life of human beings, in this way technology becomes a great benefit that presents the organisation within its broad development; a technological innovation is an element of innovation uniquely associated with technology. That is to say that technological innovation is the uniquely technical or scientific substantiation as it is established in the good or service a company or organisation. On the other hand, the work of secretaries and assistants, had a big change of a major modification in the market. Over the years, the profile of the secretary has gradually accepted its great relevance for the general maintenance of organizations. On the basis of the research carried out in the decentralized autonomous government of the canton of Vinces, we have found some techniques and skills that the secretaries carry out in the daily performance of their activities, it can be affirmed that they have quite high academic knowledge and a not very high use of technology, the secretaries show to be organized, they have a good writing skill, in such a way that there is a good organization of files, which are administered. This is all that an organisation needs to entrust it with its business and other resources.